Peningkatan Hasil Belajar Siswa pada Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning di SD - Handayani, Fitri; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the improvement of student learning outcomes in integrated thematic learning using the Discovery Learning nodel in class V SDN 15 Ulu Gadut, Padang. This research is a classroom action research with qualitative and quantitative approaches conducted in two cycles. Each cycle consists of planning, implementing, observing and reflecting. The subjects were teachers and 23 fifth grade students of SD 15 Ulu Gadut Padang city. The results of this study indicate: (1) the percentage of RPP observations in the first cycle was 83.3%, increasing to 94.4% in the second cycle. (2) Teacher activity in the first cycle was 84.4%, increasing to 96.8% in the second cycle. (3) Student activity in cycle I was 84.4%, increasing to 96.8% in cycle II. While from student learning outcomes, in the first cycle the average value was 79.7 with a percentage of completeness 60.9% increasing to 91.3 with a percentage of completeness 95.6% in the second cycle.